Self-expansion among medical students the role of medical drama doctors as models - Arbonida, Jerome Ian A.
Introduction: Currently, medical dramas are one of the most digitally accessible sources of potential role models which can influence medical students’ self-expansion despite limited face-to-face classes and clinical rotations. Objectives and Methodology: The study utilized an explanatory sequential mixed methods design. The cross-sectional survey, correlational quantitative phase data (n= 36) were merged with the descriptive qualitative data from interviews and emails (n= 8) to describe the role of medical drama doctors in medical students’ self-expansion. Results: Medical students watch medical dramas for relaxation, entertainment, information, and encouragement. For them, medical drama viewing is a multi-stage process of intention, attention, role modeling, and involvement. The results showed that their (1) overall perception of a medical drama doctor as a desirable and attainable role model who embodies competence and love (r=0.63) and (2) involvement with medical dramas (r=0.70) were the two most significant factors in achieving self-expansion. Conclusion: As medical students watch medical dramas outside the formal education settings, they feel involved and identify with those characters they perceive as role models. This leads to various images of self-expansion. Medical students are critical in learning and self-expanding themselves with positive knowledge about healthcare systems, soft skills, attitudes, and values portrayed in medical dramas. They self-expand with encouragement to be resilient, competent, and compassionate doctors. Although the response rate in the quantitative phase was low, this study hopes to widen the perspectives of educators on compassion, role modeling, and self-expansion. It is recommended that future studies increase their sample size and target other health professions population to improve generalizability.